Concept “Happiness” in the Autobiographical Prose of Vladimir Nabokov (Proceedings of Southern Federal University. Philology, 2020)
«Happiness» is one of the most significant cultural universals, semantically related to the concepts of the spiritual life of a man, the most important element performing meaning-forming and plot-forming role in an artistic work.The study of the reflection of notions about happiness in the autobiographical prose of V. Nabokov in the context of the literary and cultural situation of the first wave of Russian emigration is defined by the specifics of autobiography as a text that is created at the end of life and involves its recognition from the point of view of a person summing up intermediate or final results.The article analyzes the artistic concept «happiness» in the autobiographical prose of V. Nabokov; it determines its individual author’s content that is correlated with the general cultural content of the concept. The article is devoted to the study of the concept «happiness» as a complex emotional and value formation which reflects the universal artistic experience, recorded in the cultural memory, expresses the individual author’s understanding of the essence of objects and phenomena.The conceptual component of the word «happiness» in the creativity of V. Nabokov includes the harmonious fullness of life, freedom, the gift of creativity, the happiness of childhood, family, the hearth, the happiness of love and marriage, the enjoyment of life and its joys, a reflection of the personal history of upbringing and testing. The concept «happiness» implements not only semantic, but also axiological possibilities, reflecting both the own characteristics of the subject of the artistic image and the features of idiostyle of the writer.Key words: concept, «happiness», V. Nabokov, autobiographical prose, literature of the first wave of Russian emigration.DOI 10.18522/1995-0640-2020-2-112-121